A Beginner’s Guide to Water Management — Symbols, Abbreviations & Conversion Factors - Florida LAKEWATCH (EDIS)
This 44-page booklet provides the tools for reading, converting, interpreting and/or translating units of measure commonly used by people involved in water management in the U.S. and internationally. Much of this information is typically only available by searching numerous publications, but we have assembled it here under one cover for quick reference. This document is CIR105, is the fifth of a series of information circulars dedicated to familiarizing citizens with the language and techniques used by those involved in water management, of the Fisheries and Aquatic Sciences Department, UF/IFAS Extension. © April 2002, 2nd Edition.